Ovlia-depe: A New Parthian Site in Southern Turkmenistan (Preliminary Report) - Kurbanov, Aydogdy; Bruno, Jacopo (Anabasis. Studia Classica et Orientalia, 2020)
This report presents some preliminary results from the trial archaeological excavations in Ovlia-depe conducted from April 18 to May 19, 2011 by the researchers of the Academy of Sciences of Turkmenistan’s Institute of Archaeology and Ethnography. During the excavation, a small amount of pottery was found. Most of the pottery can be classified as wheel-made common ware, produced of medium-fine clay and fired in an oxidizing atmosphere, with the characteristic orange-red colouring of cores and surfaces. Only two fragments of grey-black ware have been found during the excavations. The different vessel types demonstrate close resemblance with similar vessels found in the main Parthian period sites of the Turkmen foothills of the Kopet Dagh and permit a tentative dating to the 2nd-1st centuries BC.